2019
DOI: 10.26773/mjssm.190305
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Coaches’ Instruction on Technical Actions, Tactical Behaviour, and External Workload in Football Small-Sided Games

Abstract: Th is study aimed to explore the eff ects of previous instruction on technical, tactical and external workload performances in football small-sided games. Two 7-a-side balanced competitive teams received instructions regarding the rules of the small-sided games proposed. Additionally, one team received instructions from the coach regarding the collective tactical behaviour required for each exercise condition: (a) Without strategic instruction (WSI); (b) Defensive strategy (DS); (c) Off ensive strategy (OS) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 24 publications
1
29
0
4
Order By: Relevance
“…The male soccer research has showed that the physiological responses of players in SSGs are affected by several external factors, such as the exercise length, rest type and period, field size, goalkeeper use, touches limitation, field surface, coaches' instructions, and coaches' incitements (Baptista et al, 2019;Castellano et al, 2013;Aguiar et al, 2012;Sarmento et al, 2018;Gonçalves et al, 2016;Olthof et al, 2015;Clemente et al, 2014;Gaudino et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The male soccer research has showed that the physiological responses of players in SSGs are affected by several external factors, such as the exercise length, rest type and period, field size, goalkeeper use, touches limitation, field surface, coaches' instructions, and coaches' incitements (Baptista et al, 2019;Castellano et al, 2013;Aguiar et al, 2012;Sarmento et al, 2018;Gonçalves et al, 2016;Olthof et al, 2015;Clemente et al, 2014;Gaudino et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Three papers [40][41][42] compared the effects of different scoring methods. Two studies [43,44] compared the effects of strategic/tactical instructions or constraints.…”
Section: Effects Of Different Task Conditionsmentioning
confidence: 99%
“…F. Clemente, H. Sarmento, Small-sided games and technical actions: a review view examined limitations in terms of the number of consecutive touches of the ball permitted [38,39], different ways of scoring [40][41][42], strategic/tactical instructions or constraints [43,44], different pitch materials [45], and different rules [46] and their effects on technical actions.…”
Section: Human Movementmentioning
confidence: 99%
“…Sportski trening kao sastavni dio trenažne tehnologije, omogućavaju transformacione procese pojedinih segmenata antropološkog statusa sportiste i usavršavanje tehničko-taktičkih elemenata, što u krajnjem vodi ka postizanju vrhunskih sportskih dostignuća. Iz ovog veoma važnog segmenta su prikazani sljedeći radovi: "Exponential versus linear tapering in junior elite soccer players: effects on physical match performance according to playing positions" (Krespi, Sporis, & Popovic, 2019), Neuromuscular adaptations after blood flow restriction training combined with nutritional supplementation: A preliminary study" (Chulvi-Medrano et al, 2019), "The Effects of High-Intensity Interval Training on Skeletal Muscle Morphological Changes and Denervation Gene Expression of Aged Rats" (Tayebi, Siahkouhian, Keshavarz, & Yousefi, 2019), "The Association between Relative Age Effect, Goals Scored, Shooting Effectiveness and the Player's Position, and her Team's Final Classification in International Level Women's Youth Handball" (Saavedra, & Saavedra, 2020), "The Effects of A 6-Week Plyometric Training Programme on Sand Versus Wooden Parquet Surfaces on the Physical Performance Parameters of Well-Trained Young Basketball Players" (Ozen, Atar, & Koc, 2020), "The Effect of an In-Season 8-Week Plyometric Training Programme Followed By a Detraining Period on Explosive Skills in Competitive Junior Soccer Players" (Branquinho et al, 2020), "Warm-Up Striding Under Load Does Not Improve 5-Km Time Trial Performance in Collegiate Cross-Country Runners" (O'Neal et al, 2020), "The influence of coaches' instruction on technical actions, tactical behaviour, and external workload in football small-sided games" (Batista et al, 2019), "The important game-related statistics for qualifying next rounds in Euroleague" (Dogan, & Ersoz, 2019) i "Normative Profile of the Efficacy and Way of Execution for the Block in Women's Volleyball from Under-14 to Elite Levels" (Echeverría, Ortega, & Palao, 2020).…”
Section: Total 30mentioning
confidence: 99%